Studies on the Digital Inclusion Among Older Adults and the Quality of Life—A Nanjing Example in China - Yang, Hui; Chen, Hongtu; Pan, Tianshu; Lin, Yiran; Zhang, Ying; Chen, Honglin (Frontiers in Public Health, 2022)
Digital inclusion can bridge the digital divide and reduce the social exclusion of the elderly. Yet, it is understudied in China. This research examines the factors influencing the digital inclusion of older adults in China and the relationship between digital inclusion and quality of life. Data collected from 312 older people (M=69.6) in Nanjing were included in a multinomial Logit model to tackle these questions. Their attitudes toward technology were the most significant factor predicting their digital inclusion. Other factors included party affiliation, living situation, personal monthly income, occupation, and capacity for instrumental activities of daily living (IADLs). This study shows digital inclusion has a direct impact on quality of life. It also serves as an intermediate variable that affects older people’s attitudes toward technology as well as their IADL capacities. Most importantly, digital inclusion promotes social integration of the elderly and improves the quality of their lives. Hence, it should not be ignored. Older people’s attitudes toward technology are one of the keys to promoting their digital inclusion.